Aplikasi Mobile Pengukuran Kwh Meter Rumah Tangga Menggunkan Arduino ESP8266 - Edwin Surya Darmawan; Anita Nathania Purbowo; Resmana Lim (Jurnal Infra, 2020)
Technology progress is so fast that everyone is using computers all the time. Making it easier for users to do something. Thus encouraging people to combine hardware and software to help in technological progress. Nowdays many things need electricity so that without electricity humans can experience great difficulties. Example smartphone is the most widely used technology and has become a very important technology in human life. But if the smartphone battry runs out, the smartphone needs to be recharged.For this reason, one solution to this problem is the existence of an pplication that can monitor the use of electrical energy in order to help humans to control electricity usage, such as a notification when excessive amounts of electricity are detected.The test results show that the factors that influence the accuracy of the photodiode Light Sensor are the light around the sensor and the blinking speed of the kWh meter. The more light around the photodiode Light Sensor, the smaller of sensitivity of the sensor and the faster of the Led on the kWh meter allows for missed sensor readings when sending data.